A Mole in Shin Bet: Lucjan Levy and Polish HUMINT Operations in Israel, 1948–1967. Issue 2 (3rd April 2022) - Gasztold, Przemysław
Abstract: From the time of the establishment of the state of Israel in 1948, many Polish Jews emigrated there, seeking shelter in the aftermath of the Holocaust and the circumstances of growing anti-Semitic attitudes. Lucjan Levy/Levi was one such emigrant who left Poland and settled in Israel. He soon joined the Shin Bet counterintelligence service, even as he remained an asset for Polish intelligence, providing Warsaw (and the intelligence services elsewhere in Eastern Europe) with valuable information on Israeli counterintelligence activity. Now, drawing on recently declassified documents, the author reconstructs Levy's intelligence performance while also examining his espionage career within the broader framework of human intelligence operations conducted by Poland's Tel Aviv Station.